Improving Reading Comprehension Through Think-Aloud Strategy - Presores, Dermaelyn J.; Tan, Jr., Jose G. Tan (Technium Social Sciences Journal, 2025)
Reading comprehension has been one of the most predominant issues especially in the field of language teaching. Hence, this research study explored the use of the Think-Aloud strategy as an intervention in improving the reading comprehension of Grade 7 students of Tagum City National Comprehensive High School. Specifically, this study seeks to determine the significant difference between the mean scores of the experimental and control groups in reading comprehension. In addition, this study employed the quasi-experimental design wherein respondents were chosen through random sampling. T-test for independent and dependent samples was utilized to determine the significant difference between the levels of reading comprehension of the control and experimental groups. Further, the researcher made use of lesson designs for the experimental group, and the daily lesson logs for the control group. The result of this study shows that there is no significant difference between the pretest mean scores of the experimental and control groups. However, after administering the post-test, both groups differed significantly, and it was the experimental group that performed better than the control group. Given all these statistical results, it was evident that the Think-Aloud strategy helps the students improve their reading comprehension. In line with the research findings, the researcher recommends elementary teachers who desire to conduct a research study may further investigate other Think-Aloud techniques in order to build more meaningful learning foundations for their learners necessary to enhance their reading comprehension as they reach a higher level of education.